The prevalence and predictors of loneliness in caregivers of people with dementia: findings from the IDEAL programme. (3rd July 2021) - Victor, Christina R.; Rippon, Isla; Quinn, Catherine; Nelis, Sharon M.; Martyr, Anthony; Hart, Nicola; Lamont, Ruth; Clare, Linda
Abstract: Objectives: To establish the prevalence of loneliness among family caregivers of people with dementia and to identify potential risk factors for loneliness. Methods: Using data from the baseline wave of the Improving the experience of Dementia and Enhancing Active Life (IDEAL) cohort study, we examined loneliness in 1283 family caregivers of people with mild-to-moderate dementia living in Great Britain. Multinomial regression was used to examine the relative influence of a series of risk factors for caregiver loneliness. Results: Almost half, 43.7%, of caregivers reported moderate loneliness and 17.7% reported severe loneliness. Greater social isolation and increased caregiving stress were linked with both moderate and severe loneliness. Better quality of relationship with the person with dementia along with increased levels of well-being and life satisfaction were associated with a lower relative risk of reporting both moderate and severe loneliness. Discussion: This study examines the prevalence and predictors of loneliness in a large sample of family caregivers of people with dementia. Notably over two-thirds of caregivers in our sample reported feeling lonely. Interventions aimed at reducing caregiving stress and supporting meaningful relationships may go some way towards helping to reduce loneliness.